3′-End processing of histone pre-mRNAs in Drosophila: U7 snRNP is associated with FLASH and polyadenylation factors - Sabath, Ivan (Cold Spring Harbor Laboratory Press, 2013)
3′-End cleavage of animal replication-dependent histone pre-mRNAs is controlled by the U7 snRNP. Lsm11, the largest component of the U7-specific Sm ring, interacts with FLASH, and in mammalian nuclear extracts these two proteins form a platform that recruits the CPSF73 endonuclease and other polyadenylation factors to the U7 snRNP. FLASH is limiting, and the majority of the U7 snRNP in mammalian extracts exists as a core particle consisting of the U7 snRNA and the Sm ring. Here, we purified the U7 snRNP from Drosophila nuclear extracts and characterized its composition by mass spectrometry. In contrast to the mammalian U7 snRNP, a significant fraction of the Drosophila U7 snRNP contains endogenous FLASH and at least six subunits of the polyadenylation machinery: symplekin, CPSF73, CPSF100, CPSF160, WDR33, and CstF64. The same composite U7 snRNP is recruited to histone pre-mRNA for 3′-end processing. We identified a motif in Drosophila FLASH that is essential for the recruitment of the polyadenylation complex to the U7 snRNP and analyzed the role of other factors, including SLBP and Ars2, in 3′-end processing of Drosophila histone pre-mRNAs. SLBP that binds the upstream stem–loop structure likely recruits a yet-unidentified essential component(s) to the processing machinery. In contrast, Ars2, a protein previously shown to interact with FLASH in mammalian cells, is dispensable for processing in Drosophila. Our studies also demonstrate that Drosophila symplekin and three factors involved in cleavage and polyadenylation—CPSF, CstF, and CF I(m)—are present in Drosophila nuclear extracts in a stable supercomplex.